2021
DOI: 10.3389/fphar.2021.777400
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Effects of Dietary Ellagic Acid Against Severe Malaria Pathogenesis by Reducing Cytokine Storms and Oxidative Stress

Abstract: Ellagic acid (EA), a fruit- and vegetable-derived flavonoid, has been reported for multiple pharmacological activities, which encouraged us to examine its useful effect in severe malaria pathogenesis, especially malaria-induced cytokine storms and oxidative stress linked to damage in major organs. Malaria was induced by injecting Plasmodium berghei–infected RBCs intraperitoneally into the mice. EA was given orally (5, 10, and 20 mg/kg) following Peter’s 4-day suppression test. EA exhibited the suppression of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The pharmacological inhibition of inflammatory mediators by natural molecules may help to reverse or slow the course of neurological complications [30] . Previous studies showed that the treatment of plant‐derived leads can reduce the production of pro‐inflammatory cytokines in the glial cell [18,31] . Dexamethasone, a reference drug is commonly used to reduce inflammation and manage neuroinflammatory disorders such as multiple sclerosis, cerebral edema, and other neurological disorders where inflammation plays a significant role [32] …”
Section: Resultsmentioning
confidence: 99%
“…The pharmacological inhibition of inflammatory mediators by natural molecules may help to reverse or slow the course of neurological complications [30] . Previous studies showed that the treatment of plant‐derived leads can reduce the production of pro‐inflammatory cytokines in the glial cell [18,31] . Dexamethasone, a reference drug is commonly used to reduce inflammation and manage neuroinflammatory disorders such as multiple sclerosis, cerebral edema, and other neurological disorders where inflammation plays a significant role [32] …”
Section: Resultsmentioning
confidence: 99%
“…Peters' four-day suppressive test was performed in infected animals in P. yoelii negresis (chloroquine-resistant strain). 40,41 After 1 hour of infection with parasites, one group of animals was given 1% DMSO in 0.7% CMC orally. The second and third groups of animals were given 0.1% DMSO in 0.7% CMC of 18b-GTA and compound-17 at doses of 5 mg kg À1 , 10 mg kg À1 , and 20 mg kg À1 relative to their body weight.…”
Section: Four-day Suppression Testmentioning
confidence: 99%
“…Briefly, serum from the experimental animals was used for measurement of alkaline phosphatase (ALP), serum glutamic oxaloacetic transaminase (SGOT), and total bilirubin using kits of the standard protocols. 40,[42][43][44] Additionally, in the same experiment, serum was derived from the blood of experimental animals collected at the peak parasitemia on day 8. The inflammatory mediators (cytokines) were quantified using mouse-specific ELISA kits (BD biosciences, USA) per manufacturer instructions.…”
Section: Biochemical Liver Function Test and Inflammatory Mediators U...mentioning
confidence: 99%
“…Depending on the redox potential in the studied reaction medium, their activity can be changed, since at low concentrations, they can act as pro-oxidants [28]. Ellagic acid is widely studied and has shown a potential therapeutic interest in the management of malaria [8]. The mechanism of action of ellagic acid is not clearly established, but it is known that the molecule, when in contact with the parasite environment, could become pro-oxidant and efficient.…”
Section: Cellular Antioxidant Activitymentioning
confidence: 99%